KEADILAN ORGANISASI SEBAGAI PEMODERASI FAKTOR-FAKTOR YANG MEMENGARUHI INTENSI KECURANGAN - Lenny Carolina M; Nazmel Nazir (Jurnal Akuntansi Trisakti, 2019)
The purpose of this research is empirically to find out the effect of management morality, effectiveness of internal control, compensation, organizational ethical culture, and organization justice as a moderating variable on intention of fraud. This research was conducted on employees who work in the finance department at companies in the Jakarta area with a sample of 150 respondents. Sampling technique used is convenience sampling. This research is included in quantitative research. Source of data in this research is primary data. Data were collected using questionnaires distributed to respondents. Data analysis method using Structural Equation Model (SEM) with WarpPLS data processing tool version 0.6Based on the results of the analysis can be concluded that effectiveness of internal control and compensation has a negative effect on intention of fraud. While Management morality and organizational ethical culture has no effect on intention of fraud. Organization justice can only weaken the negative effect of effectiveness of internal controls and compensation on intention of fraud.